Eliminating lattice defects in UiO-66-NH2 membrane towards high-precision desalination - Wenwen Dong; Jiahui Yan; Taotao Ji; Mingming Wu; Kunpeng Yu; Yi Liu; Wenjing Hu; Yi Liu (Advanced Membranes)
Zirconium-based MOF membranes exhibit significant potential in energy-efficient desalination. Nevertheless, framework defect elimination, which represents an effective protocol to enhance their molecular sieving capacity and operation stability, remains highly challenging to date. In this study, we proposed a framework defect patching strategy to prepare robust UiO-66-NH2 membrane with Zr6O4(OH)4(OAc)12 cluster source towards high-efficiency desalination. Ion sieving results indicated that increasing reaction temperature and ratio of ligand to Zr6O4(OH)4(OAc)12 cluster contributed to framework defect elimination. UiO-66-NH2 membranes prepared under optimized conditions exhibited superior metal ion rejection rate (Al3+: 97.7 ​%) and operation stability over 20 days. Particularly, their water/NaCl separation performance well exceeded majority of reported polycrystalline 3D membranes, offering promising prospects for modulating molecular diffusion kinetics in MOF pores.